Fleet based schedule optimisation for product tanker considering ship's stability - Anisa Rizvanolli; Alexander Haupt; Peter Marvin Mul̈ler; Jorin Dornemann (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: Scheduling a fleet of product tankers in a cost effective and robust way to satisfy orders is a complex task. A variety of constraints and preferences complicate this attempt. Manual solutions as common in tramp shipping are not sufficient to deliver optimal and robust schedules. Methodology: For this, we present a mixed integer linear programming formulation of the scheduling problem. Additionally intact stability calculations for each ship of the fleet are implemented in a separate program that checks the feasibility of MILP solutions and creates new cuts for the integer program. Findings: Usually the checking of the stability criteria is done before an order will be accepted and the schedule of the ship is planed accordingly. This requires the selection of a ship a priori. Checking the admissibility of a voyage gives access to a wider variety of possible combinations. Originality: To our knowledge fleet scheduling under consideration of intact stability requirements has received little attention in the literature. Previous works make very simple assumptions on the capacity of the ships and do not include in their linear pro- grams any stability models.
urn:nbn:de:gbv:830-882.054945; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Cargo scheduling in tramp shipping; Optimization; Ship stability; Mixed integer linear programming